Potential applications of deep eutectic solvents in nanotechnology: Part II - Azzouz, Amirah; Hayyan, Maan (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •DESs have promising multi-roles in the development of nano-scaled systems.•Latest studies related to DESs in nanotechnology and nanomedicine were reviewed.•Nanomaterials synthesis received the most attention.•The replacement of conventional liquids with DESs is becoming a common practice. Over the past two decades, deep eutectic solvents (DESs) have received immense interest in a wide variety of fields, including nanotechnology, due to their beneficial characteristics and the opportunity they provide, as green mixtures, to replace conventional multi-task agents with higher environmental impacts, and even ionic liquids. As such, numerous research studies have investigated the role of DESs in nano-scale applications, and their results have revealed great promise in improving not only the efficiency but also the environmental and economic aspects of many processes. Since our first review article in the field that was published in 2015, there has been a significant uptick in the number of publications reporting utilization of DESs in nanoengineering and nanobiotechnology for tasks such as nanomaterial synthesis, nanofluids, nanocatalysis, water treatment, sensing applications, nanomedicine, and others. There has also been exponential growth in these fields, raising the urgent need for a review study. This review therefore concentrates on capturing and highlighting the recent advances within these fields in order to provide a comprehensive, authoritative, and critical list covering all aspects of nano-based applications. The subject matter consists of the main applications of DESs in the aforementioned fields, covering in more detail recent advances from 2015 to the present, thus filling the later timeline gap and providing a state-of-the-art review.